Scientifically advanced solutions for chestnut ink disease - Choupina, Altino (2014)
On the north regions of Portugal and Spain, the Castanea sativa Mill. culture is extremely important. The biggest productivity and yield break occurs due to the ink disease, the causal agent being the oomycete Phytophthora cinnamomi. This oomycete is also responsible for the decline of many other plant species in Europe and worldwide. P. cinnamomi and Phytophthora cambivora are considered, by the generality of the authors, as the C. sativa ink disease causal agents. Most Phytophthora species secrete large amounts of elicitins, a group of unique highly conserved proteins that are able to induce hypersensitive response (HR) and enhances plant defense responses in a systemic acquired resistance (SAR) manner against infection by different pathogens. Some other proteins involved in mechanisms of infection by P. cinnamomi were identified by our group: endo-1,3-beta-glucanase (complete cds); exo-glucanase (partial cds) responsible by adhesion, penetration, and colonization of host tissues; glucanase inhibitor protein (GIP) (complete cds) responsible by the suppression of host defense responses; necrosis-inducing Phytophthora protein 1 (NPP1) (partial cds); and transglutaminase (partial cds) which inducts defense responses and disease-like symptoms. In this mini-review, we present some scientifically advanced solutions that can contribute to the resolution of ink disease.